Kekerasan Terhadap Anak dalam Perspektif Kriminologi Di Kecamatan Tobelo Kabupaten Halmahera Utara - Ernest Sengi; Alfonsisus Budiman (Wajah Hukum, 2020)
Children are the nation’s next generation who need to be protected from various forms of violence. The enactment of the law on the elimination of violence in household and the child protection law does not always directly proportional to the loss of violent behavior towards children. In this paper, the legal issue that will be examined is how the perspective of criminology in overcoming  violence against children in Tobelo Subdistrict North Halmahera Regency.  Then, to answer the legal issues used nondoctrinal legal research methods with a socio legal research approach that is supported by the statute approach. This approach is considered appropriate because the data on cases of violence against children in Tobelo sub-district will be described and then analyzed from this data to obtain a legal prescription on how the criminology views various forms of violence against children. The results showed that in 2015 to 2018 in Tobelo Subdistrict, North Halmahera Regency, there were 57 cases of violence against children. Besides, violence against children is a form of criminal activity in which the offender can be held liable either through general or special crimes.